Job performance and its relationship to time management among heads of sports sub-federations from the perspective of coaches (The International Journal for Scientific Research, 2025)
This research is a positive and important phenomenon in achieving planned strategic goals, as the heads of sports sub-federations influence the morale of the sports club, contributing to increased effectiveness in achieving general objectives. Members' awareness of this influence earns them respect and administrative appreciation. The research problem stems from revealing the levels of job performance of heads of sports sub-federations, which are affected by several aspects, both external and internal. To develop and improve this performance, it is necessary to understand the nature of time management by measuring the level of job performance itself and its relationship to time management among the heads of sub-federations. This allows coaches to understand the reality of their work and develop it. The research aims to identify the level of job performance and time management among heads of sports sub-federations from the coaches' perspective. The researcher used the descriptive method with correlational relationships, as it is the most efficient means of obtaining reliable knowledge. The research sample was selected purposively and consisted of players in team sports (football, volleyball, basketball, and handball) in the Al-Rifai district, totaling (60) players. The research results showed significant differences in the job performance levels of the research sample. This indicates that coaches are successfully achieving their planned objectives within the allotted timeframe. The researcher recommended providing coaches, assistant coaches, and players with intensive training courses on how to deal with external factors that affect the training process.
Keywords: Job Performance; Time Management; Team Sports